2016
DOI: 10.1016/j.enbuild.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Space heating preferences in UK social housing: A socio-technical household survey combined with building audits

Abstract: This paper provides an analysis of the relationships between dwelling, household, and motivation, behaviour and perception characteristics and winter heating setpoint temperatures (n=111) and heating periods (n=148 and 145) used in UK social housing. The work capitalises on primary data from a socio-technical household survey, undertaken in Plymouth, UK, during 2015, which was merged with building audit data collected by the social housing association managing the properties. The mean reported heating setpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 69 publications
3
30
2
Order By: Relevance
“…In addition, retrofitting domestic buildings helps improve health and comfort of occupants besides meeting the energy and fuel poverty reduction targets [6]. As a result of the thermal and economic benefits of retrofits, energy loads for space heating and thermal comfort levels in cold seasons have been the focus of research in the UK [14]. However, many studies have found that the benefits from retrofitting can be compromised through shortfalls in the building performance where achieved benefits may not necessarily resonate with the expected outcomes of the interventions [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, retrofitting domestic buildings helps improve health and comfort of occupants besides meeting the energy and fuel poverty reduction targets [6]. As a result of the thermal and economic benefits of retrofits, energy loads for space heating and thermal comfort levels in cold seasons have been the focus of research in the UK [14]. However, many studies have found that the benefits from retrofitting can be compromised through shortfalls in the building performance where achieved benefits may not necessarily resonate with the expected outcomes of the interventions [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similar studies are presented in [10]. The dependence of the room temperature set on the type of a consumer (his home, age, preferences, etc.)…”
Section: Literature Review and Problem Statementmentioning
confidence: 67%
“…It concerned those consumers who during the survey indicated that they wanted to reduce the cost of heat. According to [10], these consumers set a higher temperature than those who neither agreed nor denied the need for reducing the cost of heat. But the averaged room temperature in this study also was lower than in the project.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Unnervingly, 4% of all homes with a boiler do not have any controls at all. Research has shown that in addition to external temperature and building fabric, the key factors that influence a dwelling's space heating energy demand are the heating system's thermostat and timer settings chosen by the occupants (where such controls are available) [9]- [12].…”
Section: Introductionmentioning
confidence: 99%